Networking and Specificity-Changing DNA Methyltransferases in Helicobacter pylori - Yano, Hirokazu; Alam, Md. Zobaidul; Rimbara, Emiko; Shibata, Tomoko F.; Fukuyo, Masaki; Furuta, Yoshikazu; Nishiyama, Tomoaki; Shigenobu, Shuji; Hasebe, Mitsuyasu; Toyoda, Atsushi; Suzuki, Yutaka; Sugano, Sumio; et al. (Frontiers in Microbiology, 2020)
Epigenetic DNA base methylation plays important roles in gene expression regulation. We here describe a gene expression regulation network consisting of many DNA methyltransferases each frequently changing its target sequence-specificity. Our object Helicobacter pylori, a bacterium responsible for most incidence of stomach cancer, carries a large and variable repertoire of sequence-specific methyltransferases. By knocking out a dozen of them, we revealed they form a network controlling methylome, transcriptome and adaptive phenotype sets. The methyltransferases interact with each other in a hierarchical way, sometimes regulated positively by one methyltransferase but negatively with another. Motility, oxidative stress tolerance and DNA damage repair are likewise regulated by multiple methyltransferases. Their regulation sometimes involves translation start and stop codons suggesting coupling of methylation, transcription and translation. The methyltransferases frequently change their sequence-specificity through gene conversion of their target recognition domain and switch their target sets to remodel the network. The emerging picture of a metamorphosing gene regulation network, or firework, consisting of epigenetic systems ever-changing their specificity in search for adaptation, provides a new paradigm in understanding global gene regulation and adaptive evolution.